“This is the truth—the truth without doubt”: Textual authority and the enabling of “true” discourse in the Hindu narrative tradition of the Sivapurana - Taylor, McComas (Religions of South Asia, 2008)
In contrast with the major theistic religions, the highly decentralized Hindu traditions, for much of their history, lacked a single external authority capable of imposing standards of orthodoxy or heterodoxy on all parts of the fold. The major normative texts known as puranas are the source-books of Hindu theology, cosmology and mythology. These texts have had to compete with one another for a position of orthodoxy, and they have achieved this in part through the adoption of internal textual strategies. This paper examines one of the most important members of the genre, the Sivapurana, and identifies three such strategies. First, the discourse is placed in the mouths of three fictional meta-narrators: the deity Siva, the sage Vyasa, and his disciple Romaharsana. Second, the discourse is spiked with “power claims” relating to its own efficacy and potency. Third, strict procedures are prescribed for the public performance of the text. While not unique to the Sivapurana, the combination of meta-narration, power-claims and performative prescription all serve to elevate and valorize the text and enable it to function as “true” discourse in the Hindu episteme.